Effect of Celery (Apium graveolens L.) Microgreens on Drosophila melanogaster (Baghdad Science Journal, 2023)
Celery (Apium graveolens L. ; family : Apiaceae) was often used as a spice in daily food. However, this plant contains many antioxidant compounds useful for attenuating neurodegenerative disorders including Parkinson's disease. Planting celery in the form of microgreens harvested 15 days was expected to increase the content of bioactive compounds. In the current study, we intended to evaluate the neuromodulatory potential of methanol extract of celery microgreens on fruit flies (Drosophila melanogaster Meigen : family Drosophilidae ; ordo : Diptera) which were exposed to paraquat. Neuroprotective capacity was assessed by survival rate, locomotor performance, lipid peroxidation and dopamine content after being treated with 120 µg/mL extract of celery microgreens and 3.5 mM paraquat for 4 days. Phytochemical constituents from extract of celery microgreens were measured including total polyphenol content and antioxidant activity using the radicals scavenging method. Exposure of adult fruit flies to paraquat will cause a decrease in the survival and locomotor phenotype improved by extract of celery microgreens treatment. In parallel, increased malondialdehyde content from lipid peroxidation and decreased dopamine content can be improved by the presence of celery microgreens extract. Neuroprotective capacities indicate a high content of antioxidant compounds of celery microgreens extract. Our study concludes that celery microgreens exhibited to retard the effect of oxidative stress that causes Parkinson's disease.